2020
DOI: 10.1016/j.ejmech.2020.112116
|View full text |Cite
|
Sign up to set email alerts
|

Targeting different binding sites in the CFTR structures allows to synergistically potentiate channel activity

Abstract: Recent evidence shows that combination of correctors and potentiators, such as the drug ivacaftor (VX-770), can significantly restore the functional expression of mutated Cystic Fibrosis Transmembrane conductance Regulator (CFTR), an anion channel which is mutated in cystic fibrosis (CF). The success of these combinatorial therapies highlights the necessity of identifying a broad panel of specific binding mode modulators, occupying several distinct binding sites at structural level. Here, we identified two sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 95 publications
(112 reference statements)
0
14
1
Order By: Relevance
“…Important to note, the validity of the proposed pipeline can be already assessed retrospectively, by evaluating the degree of consensus of the prediction and results obtained with the various techniques employed. In effect, already reported cases of this consensus are: computational predictions vs. SPR [52] or vs. cell-based assays [49], immunoprecipitation vs. overlay assays or vs. SPR [70], SPR vs. thermostability assays or vs. cell-based assays [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important to note, the validity of the proposed pipeline can be already assessed retrospectively, by evaluating the degree of consensus of the prediction and results obtained with the various techniques employed. In effect, already reported cases of this consensus are: computational predictions vs. SPR [52] or vs. cell-based assays [49], immunoprecipitation vs. overlay assays or vs. SPR [70], SPR vs. thermostability assays or vs. cell-based assays [48].…”
Section: Discussionmentioning
confidence: 99%
“…Among the computational models listed above, only a few have been used to better characterize the binding mode of known F508del-CFTR-rescuing drugs, to virtually screen libraries of molecules aimed at the identification of new putative F508del-CFTR-binding compounds or to design new CFTR-targeted drugs [48,49]. On the contrary, a huge amount of computational studies has been developed in the attempt of clarifying at a molecular level the mechanism of action of F508del-CFTR-ligands, using several NBDs RX data [23,[50][51][52] or the more recent cryo EM structures [53].…”
Section: Cftr Computational Modelsmentioning
confidence: 99%
“…As the concentration of intracellular chloride ion increases, Protein Kinase a (PKa) is activated, causing the channel to open (19). Similarly, the extracellular chloride concentration also regulates channel gating, and increased concentrations of extracellular chloride promote the opening of channels (20). Thus, CFTR facilitates two-way permeability of chloride ions (20).…”
Section: Mutations Of the Cystic Fibrosis Transmembrane Conductance Rmentioning
confidence: 99%
“…Similarly, the extracellular chloride concentration also regulates channel gating, and increased concentrations of extracellular chloride promote the opening of channels ( 20 ). Thus, CFTR facilitates two-way permeability of chloride ions ( 20 ). Previous studies have suggested that, in addition to regulating chloride ion transport through epithelial cells, CFTR is involved in the regulation of various ion transporters, including epithelial sodium channels, chloride/bicarbonate exchangers, sodium/proton exchangers and water channels ( 20 22 ).…”
Section: Overview Of Cftr Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation